2002
DOI: 10.1073/pnas.082666399
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of internal water molecules in rhodopsin revealed by x-ray crystallography

Abstract: Activation of G protein-coupled receptors (GPCRs) is triggered and regulated by structural rearrangement of the transmembrane heptahelical bundle containing a number of highly conserved residues. In rhodopsin, a prototypical GPCR, the helical bundle accommodates an intrinsic inverse-agonist 11-cis-retinal, which undergoes photo-isomerization to the all-trans form upon light absorption. Such a trigger by the chromophore corresponds to binding of a diffusible ligand to other GPCRs. Here we have explored the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
899
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 681 publications
(939 citation statements)
references
References 41 publications
37
899
0
2
Order By: Relevance
“…This restoration of ligand binding by reciprocal mutation demonstrates that the side-chains of the two residues in TMs 2 and 7 have complementary roles in maintaining the structure of the receptor and occupy the same microenvironment within the receptor helical bundle. Subsequently, the crystal structure of bovine rhodopsin revealed that these residues are capable of interacting through a water molecule [110] thus validating the GnRH receptor models. Interestingly, this exchange prevents the human GnRH receptor coupling to phospholipase D by the small G-proteins ARF and RhoA, implying receptor conformationdependent signaling selectivity [98].…”
Section: Gnrh Receptor Structure and Functionmentioning
confidence: 76%
“…This restoration of ligand binding by reciprocal mutation demonstrates that the side-chains of the two residues in TMs 2 and 7 have complementary roles in maintaining the structure of the receptor and occupy the same microenvironment within the receptor helical bundle. Subsequently, the crystal structure of bovine rhodopsin revealed that these residues are capable of interacting through a water molecule [110] thus validating the GnRH receptor models. Interestingly, this exchange prevents the human GnRH receptor coupling to phospholipase D by the small G-proteins ARF and RhoA, implying receptor conformationdependent signaling selectivity [98].…”
Section: Gnrh Receptor Structure and Functionmentioning
confidence: 76%
“…One internal water molecule was included in the receptor model, which was located in proximity to D2.50 and linked helices 2, 3 and 7 at a comparable position as water molecule 1b in the structure of bovine rhodopsin [26].…”
Section: Resultsmentioning
confidence: 99%
“…Different to the model of Sippl et al which suggested an indirect influence of amino-acids varying between species, in the model of Yao antagonists made a direct contact to those residues, resulting in a ligand placement extending from D3.32 orthogonal to the membrane plane down to residue D2.50 [25,26]. In 2005, a model of the rat H 3 R was published by Lorenzi et al which was used to guide the successful design of further imidazole-containing H 3 R compounds [27].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…structures have been elucidated (1)(2)(3). Rhodopsin has an extracellular N-terminal domain, seven transmembrane helices (TMs) connected by alternating intracellular and extracellular hydrophilic loops and an intracellular C-terminal domain.…”
mentioning
confidence: 99%